HISTORY OF THE SOCIAL CONDITION OF UZBEKISTAN ON THE EVE OF INDEPENDENCE - Mukhsin Moydinovich Kholmatov; Amanov Abdusalim Abdusalomovich (Web of Journals Publishing, 2023)
This article deals with the reappearance of serious social problems in the last years of the former Soviet Union in Fergana region their reasons and the solution of these problems during the years of independence under the guidance of I.A.Karimov.
Keywords: Social problem, financial crisis